At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve this problem, we need to make the function [tex]\( f(x)=x^2+3 \)[/tex] one-to-one by restricting its domain and then find its inverse.
First, let's understand why the function [tex]\( f(x)=x^2+3 \)[/tex] is not one-to-one on its natural domain. By definition, a function is one-to-one if every value in its domain maps to a unique value in its range.
Consider [tex]\( f(x) = x^2 + 3 \)[/tex]:
- For [tex]\( x = -2 \)[/tex], [tex]\( f(-2) = 4 + 3 = 7 \)[/tex]
- For [tex]\( x = 2 \)[/tex], [tex]\( f(2) = 4 + 3 = 7 \)[/tex]
Since different values of [tex]\( x \)[/tex] (specifically, [tex]\( -2 \)[/tex] and [tex]\( 2 \)[/tex]) produce the same value of [tex]\( f(x) \)[/tex] (which is [tex]\( 7 \)[/tex]), the function is not one-to-one over the entire real number line.
To make [tex]\( f(x) \)[/tex] one-to-one, we need to restrict its domain.
### Exploring Possible Restrictions
Let's evaluate the given options one by one:
#### 1. Domain: [tex]\( x \leq 0 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
- When [tex]\( x \leq 0 \)[/tex], [tex]\( f(x) \leq 3 \)[/tex].
- However, [tex]\( \sqrt{x-3} \)[/tex] is only defined for [tex]\( x \geq 3 \)[/tex], leading to a contradiction since [tex]\( x-3 \)[/tex] is non-negative only if [tex]\( x \geq 3 \)[/tex].
#### 2. Domain: [tex]\( x \geq 0 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x+3} \)[/tex]
- With [tex]\( x \geq 0 \)[/tex], [tex]\( f(x) \geq 3 \)[/tex].
- However, the inverse should undo the function [tex]\( f(x) = x^2 + 3 \)[/tex]. Here, [tex]\( \sqrt{x+3} \)[/tex] does not represent this inversion correctly, as [tex]\( x + 3 \)[/tex] should not be the term under the square root.
#### 3. Domain: [tex]\( x \geq 0 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
- When [tex]\( x \geq 0 \)[/tex], [tex]\( f(x) \geq 3 \)[/tex].
- For the inverse, we start with [tex]\( y = x^2 + 3 \)[/tex], and solving for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex] gives [tex]\( x = \sqrt{y-3} \)[/tex]. Therefore, this works.
#### 4. Domain: [tex]\( x \geq 3 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
- If the domain is [tex]\( x \geq 3 \)[/tex], we're not starting from the logical definition of the quadratic expression's domain restriction from [tex]\( x\geq0 \)[/tex].
### Conclusion
The correct way to restrict the domain so that the function is one-to-one and find its inverse is:
- Restricted domain: [tex]\( x \geq 0 \)[/tex]
- Inverse function: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
Thus, the valid solution is:
[tex]\[ \text{Restricted domain: } x \geq 0, \quad f^{-1}(x) = \sqrt{x-3} \][/tex]
First, let's understand why the function [tex]\( f(x)=x^2+3 \)[/tex] is not one-to-one on its natural domain. By definition, a function is one-to-one if every value in its domain maps to a unique value in its range.
Consider [tex]\( f(x) = x^2 + 3 \)[/tex]:
- For [tex]\( x = -2 \)[/tex], [tex]\( f(-2) = 4 + 3 = 7 \)[/tex]
- For [tex]\( x = 2 \)[/tex], [tex]\( f(2) = 4 + 3 = 7 \)[/tex]
Since different values of [tex]\( x \)[/tex] (specifically, [tex]\( -2 \)[/tex] and [tex]\( 2 \)[/tex]) produce the same value of [tex]\( f(x) \)[/tex] (which is [tex]\( 7 \)[/tex]), the function is not one-to-one over the entire real number line.
To make [tex]\( f(x) \)[/tex] one-to-one, we need to restrict its domain.
### Exploring Possible Restrictions
Let's evaluate the given options one by one:
#### 1. Domain: [tex]\( x \leq 0 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
- When [tex]\( x \leq 0 \)[/tex], [tex]\( f(x) \leq 3 \)[/tex].
- However, [tex]\( \sqrt{x-3} \)[/tex] is only defined for [tex]\( x \geq 3 \)[/tex], leading to a contradiction since [tex]\( x-3 \)[/tex] is non-negative only if [tex]\( x \geq 3 \)[/tex].
#### 2. Domain: [tex]\( x \geq 0 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x+3} \)[/tex]
- With [tex]\( x \geq 0 \)[/tex], [tex]\( f(x) \geq 3 \)[/tex].
- However, the inverse should undo the function [tex]\( f(x) = x^2 + 3 \)[/tex]. Here, [tex]\( \sqrt{x+3} \)[/tex] does not represent this inversion correctly, as [tex]\( x + 3 \)[/tex] should not be the term under the square root.
#### 3. Domain: [tex]\( x \geq 0 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
- When [tex]\( x \geq 0 \)[/tex], [tex]\( f(x) \geq 3 \)[/tex].
- For the inverse, we start with [tex]\( y = x^2 + 3 \)[/tex], and solving for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex] gives [tex]\( x = \sqrt{y-3} \)[/tex]. Therefore, this works.
#### 4. Domain: [tex]\( x \geq 3 \)[/tex]; Inverse: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
- If the domain is [tex]\( x \geq 3 \)[/tex], we're not starting from the logical definition of the quadratic expression's domain restriction from [tex]\( x\geq0 \)[/tex].
### Conclusion
The correct way to restrict the domain so that the function is one-to-one and find its inverse is:
- Restricted domain: [tex]\( x \geq 0 \)[/tex]
- Inverse function: [tex]\( f^{-1}(x)=\sqrt{x-3} \)[/tex]
Thus, the valid solution is:
[tex]\[ \text{Restricted domain: } x \geq 0, \quad f^{-1}(x) = \sqrt{x-3} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.